2009
DOI: 10.1089/zeb.2009.0613
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Heritable Model of Testicular Germ Cell Tumor in the Zebrafish

Abstract: Germ cell tumors (GCTs) affect infants, children and adults and are the most common cancer type in young men. Progress in understanding the molecular basis of germ cell tumors has been hampered by a lack of suitable animal models. Here we report the identification of a zebrafish model of highly penetrant, heritable testicular germ cell tumor isolated as part of a forward-genetic screen for cancer-susceptibility genes. The mutant line develops spontaneous testicular tumors at a median age of 7 months, and pedig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 44 publications
1
44
0
Order By: Relevance
“…Previously, we described the identification of a zebrafish model of heritable testicular GCT during a forward genetic screen to identify cancer susceptibility genes (17). Adult homozygous and heterozygous males from the testicular germ-cell tumor (tgct) mutant line develop gonadal tumors consisting of large, primitive germ cells (Fig.…”
Section: Testicular Tumors Of Premeiotic Germ Cells Develop In Tgct Mmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, we described the identification of a zebrafish model of heritable testicular GCT during a forward genetic screen to identify cancer susceptibility genes (17). Adult homozygous and heterozygous males from the testicular germ-cell tumor (tgct) mutant line develop gonadal tumors consisting of large, primitive germ cells (Fig.…”
Section: Testicular Tumors Of Premeiotic Germ Cells Develop In Tgct Mmentioning
confidence: 99%
“…However, the multiplicity of ligands, receptors, and cell types involved has made elucidation of specific signaling events difficult. We previously described a zebrafish mutant that develops highly penetrant, dominantly inherited testicular GCTs (tgct) (17). Here we report that a mutation in activin receptor-like kinase 6b (alk6b), the zebrafish homolog to human Bmpr1b, is responsible for the TGCT phenotype.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Several labs have performed screens in zebrafish to uncover cancer-related genes. Work from the Zon lab utilized phosphorylated histone H3 staining, a marker of proliferation, in a cell cycle screen to identify cancer prone mutants (Shepard et al 2005, Neumann et al 2009). These studies identified a zebrafish mutant of separase (also known as espl1, extra spindle poles like 1), an anaphase promoting cysteine protease (Shepard et al 2007).…”
Section: Forward Genetic Screensmentioning
confidence: 99%
“…These mutant zebrafish exhibited genome instability and increased cancer susceptibility. The cell cycle screen also identified a zebrafish model of germ cell tumors (Neumann et al 2009). Zebrafish harboring a mutation in laminin, g 1 (lamc1) exhibited, both spontaneous and carcinogen-induced, germ cell tumors.…”
Section: Forward Genetic Screensmentioning
confidence: 99%